Characteristics of pneumonia in children with suspected/confirmed COVID-19 - Rizal Marubob Silalahi; Wisman Dalimunthe; Rita Evalina; Juliandi Harahap; Bidasari Lubis; Inke Nadia D. Lubis (Indonesian Pediatric Society, 2023)
Background The most common COVID-19 infection clinical features in pediatric patients are similar to those of other pulmonary diseases, i.e., fever, cough, and shortness of breath. Information about the characteristics of coinfection and superinfection in COVID-19 cases can reduce misdiagnosis and differentiate COVID-19 from other pulmonary infections. Objective To observe the characteristics of pneumonia in children with suspected/confirmed COVID-19. Methods This descriptive study used medical record data of children hospitalized from 1 January 2020 – 31 January 2021 to describe the characteristics of pneumonia in suspected and confirmed COVID-19 cases in Haji Adam Malik Hospital, Medan, North Sumatra. Pneumonia-related findings, such as clinical symptoms, chest X-ray, and blood test results,were collected. Results There were 27 confirmed and 34 suspected COVID-19 children. Most of them were aged 6 to 8 years. Pneumonia was significantly associated with COVID-19. In confirmed COVID-19 cases, fever persisted after 3 days, with cough and shortness of breath. Patients did not have flu symptoms, but had below normal SpO2 (81-90%). The occurrence of lung rhonchi was significant in confirmed COVID-19 group. Chest X-ray results showed lung opacity in all confirmed COVID-19 patients. Mean white blood cell (WBC) count was significantly lower in COVID-19 confirmed (3.49x103/µL) vs. suspected group (17.9 x103/µL) (P=0.011). Mean CRP was significantly higher in COVID-19 confirmed (26.5 mg/L) vs. suspected group (4 mg/L). Conclusion Pneumonia with confirmed COVID-19 cases present with longer fever and lower SpO2. Patients are presented with lung ronchi, had lower WBCcount, and higher CRP. Chest X-ray shows opacity and consolidation.